A Review of the Development and Clinical Application Progress of Dental Adhesive Materials - Meng, Fei; Chen, Yang (International Journal of Materials Science and Technology Studies, 2025)
Dental adhesive materials are one of the core technologies in modern restorative dentistry. Their development has evolved from mechanical retention to chemical bonding, and from single function to multi-functional composites. This article reviews the development history of dental adhesive materials, including advancements in etch-and-rinse techniques, self-etch adhesive systems, and universal adhesives. It also explores their clinical application progress in various fields such as caries restoration, aesthetic restoration, and implant restoration. Furthermore, the article analyzes the current limitations of adhesive materials and future development trends, providing references for clinical selection and research.